Homostructured negative differential resistance device based on zigzag phosphorene nanoribbons. Issue 50 (4th June 2015) - Zhang, Chenhui; Xiang, Gang; Lan, Mu; Tang, Zhijie; Deng, Lidong; Zhang, Xi
<x xml:space="preserve">Abstract</x> Robust negative differential resistance as well as quite large currents are observed in zigzag phosphorene nanoribbon homostructures.